Assessment of urate-lowering therapies on lipid metabolism and kidney function in non-dialysis chronic kidney disease patients: 12 months multicenter cohort study - Waheed, Yousuf Abdulkarim; Yin, Huanhuan; Liu, Jie; Almayahe, Shifaa; Bishdary, Maryam; Munisamy Selvam, Karthick Kumaran; Farrukh, Syed Muhammad; Li, Shulin; Wang, Disheng; Zhou, Xinglei; Sun, Dong (Frontiers in Endocrinology, 2025)
Background and objectivesUrate lowering therapies (ULTs) are primarily used to manage hyperuricemia (HUA), which refers to an increase in serum uric acid (SUA) levels. SUA is an important marker for assessing kidney function in patients complicated with chronic kidney disease (CKD). Recent studies revealed a close relationship between SUA and lipid metabolism. We aim to investigate the impact of ULTs on kidney function and lipid profiles in CKD patients, and further explore the sex-specific ULTs effects on lipid profiles.MethodWe conducted a multicenter, prospective observational cohort study, enrolled n=200 patients aged between 20 and 80 years old with stages 3/4 CKD. Patients were divided into two groups: the ULT group (n=94) who were receiving febuxostat or allopurinol, and the Non-ULT group (n=106) who were receiving their conventional CKD therapy, the study employed clinically indicated allocation. ULT initiation was based on physician judgment per guidelines persistent HUA with SUA ≥7 mg/dL in males and ≥6 mg/dL in females with CKD progression risk factors. Models adjusted for all collected confounders, renal function including estimated glomerular filtration rate (eGFR), serum creatinine (Scr), blood urea nitrogen (BUN), and SUA, and lipid profiles including high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), triglyceride (TG), and total cholesterol (TC). Results remained consistent in sensitivity analyses stratifying by baseline characteristics. Subgroups were further analyzed based on sex, to evaluate sex-specific differences in lipid metabolism related to ULTs. All participants went through clinical assessment before and after treatment and were followed for 12 consecutive months.ResultsLDL-c significantly decreased in the ULT group compared to the Non-ULT group after 12 months of observation (2.14 ± 0.32 vs. 2.42 ± 0.32 [95% CI: -0.36 to -0.18], P<0,001). Similarly, TC and TG were significantly decreased in the ULT group compared to the Non-ULT group after 12 months of observation (4.18 ± 0.44 vs. 4.47 ± 0.39 [95% CI: -0.40 to -0.16], P<0,001) for TC, and (2.43 ± 0.62 vs. 2.63 ± 0.58 [95% CI: -0.37 to -0.03], P<0,016) for TG. Moreover, HDL-c increased significantly in the ULT group compared to the Non-ULT group (1.41 ± 0.13 vs. 1.23 ± 0.15 [95% CI: 0.13 to 0.21], P<0.001). The sex-specific ULT on lipid profiles exhibited a greater reduction in LDL-c in males by (-0.28 mmol/L [95% CI: -0.32 to -0.14], P<0.001), and a more pronounced increase in HDL-c levels by (+0.23 mmol/L [95% CI: 0.07 to 0.18], P<0.001). A significant correlation was observed Pre- and Post-treatment between SUA and LDL-c/HDL-c, Post-treatment LDL-c (R=0.2942, R²=0.2639, 95% CI: [0.0974 to 0.4689], P<0.0040), Post-treatment HDL-c (R=-0.3935, R²=0.1548, 95% CI: [-0.5521 to -0.2074], P<0.0001). SUA significantly decreased in the ULT group compared to the Non-ULT group after 12 months of treatment (398.55 ± 45.48 vs. 456.66 ± 38.23 [95% CI: -69.78 to -46.42], P<0.001). Similarly, eGFR slightly improved in the ULT group compared to the Non-ULT after 12 months of treatment (40.83 ± 7.50 vs. 34.43 ± 7.68 [95% CI: 4.32 to 8.51], P<0.001). These results indicate the renoprotective effects of ULTs in CKD patients.ConclusionIn this cohort study of non-dialysis CKD patients, ULT use was associated with improved lipid profiles reduced LDL-c, TG, and TC; increased HDL-c, with greater HDL-c elevation and LDL-c reduction in males. ULTs exposure also correlated with attenuated CKD progression. These findings suggest potential interactions between SUA and lipid metabolism, highlighting ULTs’ possible role in managing dyslipidemia and renal function decline in pre-dialysis CKD.